2014
DOI: 10.1177/2041731414543965
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic cell culture on calcium phosphate microcarriers for bone tissue engineering applications

Abstract: Developing appropriate cell culturing techniques to populate scaffolds has become a great challenge in tissue engineering. This work describes the use of spinner flask dynamic cell cultures to populate hydroxyapatite microcarriers for bone tissue engineering. The microcarriers were obtained through the emulsion of a self-setting aqueous α-tricalcium phosphate slurry in oil. After setting, hydroxyapatite microcarriers were obtained. The incorporation of gelatin in the liquid phase of the α-tricalcium phosphate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 36 publications
2
30
0
Order By: Relevance
“…Our results indicated that hASCs were able to adhere to LFAMs in less than 2 h, under suitable conditions. In particular, the dynamic seeding of cells provided the best outcomes in comparison with static cultures, in terms of cell adhesion and viability, confirming previously published literature findings [64,65]. Moreover, the modality of the dynamic culture—intermittent or not—deeply influences final cell adhesion and subsequent expansion and differentiation.…”
Section: Discussionsupporting
confidence: 86%
“…Our results indicated that hASCs were able to adhere to LFAMs in less than 2 h, under suitable conditions. In particular, the dynamic seeding of cells provided the best outcomes in comparison with static cultures, in terms of cell adhesion and viability, confirming previously published literature findings [64,65]. Moreover, the modality of the dynamic culture—intermittent or not—deeply influences final cell adhesion and subsequent expansion and differentiation.…”
Section: Discussionsupporting
confidence: 86%
“…4 They possess unique properties, including good osteoconductivity, biocompatibility, and injectability, and have found increasing applications in regenerative therapies. [4][5][6][7][8][9] We previously reported that calcium hydroxyapatite (HA)-based CPCs promoted growth and differentiation in human DPSCs. 5 However, CPCs are difficult to use alone as pulp-capping agents because they have limited antibacterial activity, long curing times, and low compressive strength.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, turbulent forces and shear stress could be created, inducing cell sufferance. In such a bioreactor the Saos-2 osteoblastic cell line was shown to attach to HA-incorporating microcarriers and proliferate in a more efficient way than when the microcarriers were kept in static conditions [127]. Seeded into a decellularized bone-derived scaffold, adipose tissue-derived stem cells are able to adhere, migrate, grow and differentiate into osteoblastic cells expressing ALP.…”
Section: Bioreactors Applied To Bone Tissue Engineeringmentioning
confidence: 99%